Social activities and long-term depressive-symptoms trajectories among middle-aged and older adults in China: a population-based cohort study - Lin, Xuhui; Liu, Siyue; Hu, Zhao; Xu, Huilan (Frontiers in Psychiatry, 2023)
The association between social activities and depressive symptoms remains unclear.This study aimed to explore the relationship between social activities at baseline and the longterm depressive-symptoms trajectories among a cohort of middle-aged and older adults in China.: This study included 13,258 participants aged 45 years and older from the China Health and Retirement Longitudinal Study (CHARLS). Depressive symptoms across four waves from 2011 to 2018 were evaluated using the 10-item Center for Epidemiologic Studies Depression Scale (CESD-10). Four types of social activities were assessed at baseline by self-report: (1) interacting with friends; (2) playing Mahjong, chess, and cards or attending a community club; (3) providing help to family, friends, or neighbors; and (4) attending a sporting or social event or club.Group-based trajectory modeling (GBTM) was used to map depressive-symptoms trajectories during the follow-up period.Results: Not interacting with friends at baseline was associated with an increased risk of increasing (adjusted odds ratio [aOR]: 1.21, 95% confidence interval [CI]: 1.03, 1.41) and severestable (aOR: 1.35, 95% CI: 1.10, 1.65) depressive-symptoms trajectories. Participants who did not play Mahjong, cards, or chess and did not attend a sporting or social event or club at baseline were more likely to have mild-stable, decreasing, increasing, and severe-stable depressivesymptoms trajectories.Social activities play an important role in long-term depressive-symptoms trajectories in middle-aged and older Chinese adults. Interacting with friends, attending sports, or social clubs may prevent depressive symptoms.